Community Policing in Schools: Relationship-Building and the Responsibilities of School Resource Officers. (9th September 2019) - Broll, Ryan; Howells, Stephanie
Abstract: School resource officers (SROs) have become nearly ubiquitous in North American schools in the last three decades. Most research on SROs has examined their impact on violence and disorder at school, yielding mixed results; however, it is widely accepted that traditional law enforcement responsibilities comprise only one element of SROs' triad of responsibilities, which also includes teaching and counselling. Although their responsibilities are based in community policing models, little research has explored the place of community policing principles within the work of SROs. Drawing upon mixed methods data collected from school administrators and SROs in a large Canadian city, this study examines relationship-building within the context of SROs' triad of responsibilities. The results suggest that SROs follow a community policing approach and strategically foster mutually beneficial relationships to support their law enforcement, teaching, and counselling objectives. Further, as a result of their established relationships, SROs are positioned as key sources of support for school administrators.